Information System for Submitting Payment for Operational Costs of PT Selamat Makmur in Tangerang - St Wulan Aprianti; Agus Junaidi (Informatics and Software Engineering, 2025)
Challenges arise from the manual submission of operational cost payments using Microsoft Excel. This manual process is susceptible to issues in payment submissions, complicates the tracking of approved payments, and lacks automated payment reminders. The author utilizes two approaches: the Data Collection method and the Software Development method. The Data Collection method entails conducting observations, interviews, and literature reviews. In regards to software development, the waterfall model is highlighted for its straightforward, sequential implementation. By adopting this system, PT. Selamat Makmur aims to streamline the submission and payment of operational costs, reduce errors, and improve transparency and accuracy throughout the company's operational cost management. This system is also vital for ensuring the efficient functioning of the cosmetic production process and supporting the company's growth in a competitive market.